2020
DOI: 10.1108/jbim-10-2018-0291
|View full text |Cite
|
Sign up to set email alerts
|

The concept of intelligent agent in business interactions: is virtual assistant an actor or a boundary object?

Abstract: Purpose Interactions are fundamental for successful relationships and stable cooperation in a business-to-business market. The main assumption in research on interactions, so obvious that usually not stated by researchers, is that they are set between humans. The development of artificial intelligence forces the re-examination of this assumption. This paper aims to conceptualize business virtual assistants (BVAs), a type of intelligent agent, as either a boundary object or an actor within business interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…A strategy for directing a call between a guest and an intelligent voice reaction (IVR) framework, the guest utilizing a gadget to lead the call, the gadget arranged to execute a menial helper, the technique involving utilizing the remote helper to lead the call at any rate to some degree by impacting the style of data given to the guest during the call as well as the substance of data went between the gadget and the IVR [8] framework during the call. In intelligent virtual assistant, Intelligent techniques are not only used in day to day interaction like play music and open an application but also in business interaction [9]. IVAs advanced from chatbots, programming specialists customized to banter with people through either text or voice.…”
Section: -Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A strategy for directing a call between a guest and an intelligent voice reaction (IVR) framework, the guest utilizing a gadget to lead the call, the gadget arranged to execute a menial helper, the technique involving utilizing the remote helper to lead the call at any rate to some degree by impacting the style of data given to the guest during the call as well as the substance of data went between the gadget and the IVR [8] framework during the call. In intelligent virtual assistant, Intelligent techniques are not only used in day to day interaction like play music and open an application but also in business interaction [9]. IVAs advanced from chatbots, programming specialists customized to banter with people through either text or voice.…”
Section: -Related Workmentioning
confidence: 99%
“…Better infrastructure to selective locations can be provided after an analysis of tourist's footfall data. The emergency button in our watch or smartphone can provide a timely response from the hospital [9], fire department, police, etc. Automate health devices can send an alert to your doctor directly if an abnormal health condition is observed like high sugar level, high blood pressure, etc.…”
Section: -Trust Issues In Intelligent Virtual Assistantmentioning
confidence: 99%
“…They can bring to light a firm's corporate expertise and social responsibilities and imply that the company has fulfilled clients' expectations and desires (Trivedi, 2020;Alam, 2020). In particular, the reputation of multinational corporations is often granted priority in industrial marketing context (Kot, 2020). In the main this form of study is based not just on new but rather on developed markets, while there are exceptions (Onufre & Bergek, 2020).…”
Section: Brand Imagementioning
confidence: 99%
“…It can radically improve an existing company's operations and create a space for entirely new businesses (Dadouchi and Agard, 2018;Davenport et al, 2020;Dwivedi et al, 2020;Grover et al, 2020;Pillai et al, 2020;Wilson and Bettis-Outland, 2019). Notably, there is increasing interest in the application of AI technologies to B2B marketing innovation (Kot and Leszczyński, 2020;Dong et al, 2014;Tan et al, 2012;Hosseini et al, 2010;Gessner and Scott, 2009). For instance, a survey conducted by Google and MIT Technology Review collected data from over 1,400 executives and found that industrial marketing services ranked among the top areas regarding the implementation of AI for innovation (Simonite, 2018).…”
Section: Introductionmentioning
confidence: 99%